Access to Subspecialty Care And Survival Among Patients With Liver Disease. (June 2016) - Mellinger, Jessica L; Moser, Stephanie; Welsh, Deborah E; Yosef, Matheos T; Van, Tony; McCurdy, Heather; Rakoski, Mina O; Moseley, Richard H; Glass, Lisa; Waljee, Akbar K; Volk, Michael L; Sales, Anne; et al.
Abstract : OBJECTIVES: Access to subspecialty care may be difficult for patients with liver disease, but it is unknown whether access influences outcomes among this population. Our objectives were to determine rates and predictors of access to ambulatory gastrointestinal (GI) subspecialty care for patients with liver disease and to determine whether access to subspecialty GI care is associated with better survival. METHODS: We studied 28, 861 patients within the Veterans Administration VISN 11 Liver Disease cohort who had an ICD‐9‐CM diagnosis code for liver disease from 1 January 2000 through 30 May 2011. Access was defined as a completed outpatient clinic visit with a gastroenterologist or hepatologist at any time after diagnosis. Multivariable logistic regression was used to determine predictors of access to a GI subspecialist. Survival curves were compared between those who did and those who did not see a specialist, with propensity score adjustment to account for other covariates that may affect access. RESULTS: Overall, 10, 710 patients (37%) had a completed GI visit. On multivariable regression, older patients (odds ratio (OR) 0.98, P <0.001), those with more comorbidities (OR 0.98, P =0.01), and those living farther from a tertiary‐care center (OR 0.998/mi, P <0.001) were less likely to be seen in clinic. Patients who were more likely to be seen included those who had hepatitis C (OR 1.5, P <0.001) or cirrhosis (OR 3.5, P <0.001) diagnoses prior to their initial visit. Patients with an ambulatory GI visit at any time after diagnosis were less likely to die at 5 years when compared with propensity‐score‐matched controls (hazard ratio 0.81, P <0.001). CONCLUSIONS: Access to ambulatory GI care was associated with improved 5‐year survival for patients with liver disease. Innovative care coordination techniques may prove beneficial in extending access to care to liver disease patients.